2014
DOI: 10.1002/rmv.1802
|View full text |Cite
|
Sign up to set email alerts
|

Global protein profiling studies of chikungunya virus infection identify different proteins but common biological processes

Abstract: Chikungunya fever (CHIKF) caused by the mosquito-transmitted chikungunya virus (CHIKV) swept into international prominence from late 2005 as an epidemic of CHIKF spread around countries surrounding the Indian Ocean. Although significant advances have been made in understanding the pathobiology of CHIKF, numerous questions still remain. In the absence of commercially available specific drugs to treat the disease, or a vaccine to prevent the diseases, the questions have particular significance. A number of studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 127 publications
3
4
0
Order By: Relevance
“…. This again supports a previous proposal that studies that investigate differentially expressed proteins are likely to identify different proteins but may highlight common biological processes .…”
Section: Studiessupporting
confidence: 90%
“…. This again supports a previous proposal that studies that investigate differentially expressed proteins are likely to identify different proteins but may highlight common biological processes .…”
Section: Studiessupporting
confidence: 90%
“…Quantitative proteomics strategies have been used previously to study the effects of CHIKV infection in cell culture, mice, and patient serum (for a recent review see ). 2D‐DGE and 2D‐DIGE approaches identified between 15 and 51 differentially expressed proteins.…”
Section: Introductionmentioning
confidence: 99%
“…A number of proteomics studies have been carried out in CHIKV infection previously (Table 2), and the results were compared in a recent review by Smith [17]. All the four major pathways that we have identified in our study have been found to be modulated during CHIKV infection in one or more of these earlier studies.…”
Section: Common Set Of Pathways and Proteins Modulated In Chikv Infecmentioning
confidence: 69%
“…These include studies using cell lines like CHME-5, a microglial cell [9], WRL-68, a human hepatic fetal epithelial cell line [10] and SJCRH30, a human rhabdomyosarcoma cell line [11], and those in patient serum [12], in white blood cells isolated from Chikungunya fever patients [13] and in experimentally infected mice tissues such as the liver, brain and muscle [14][15][16]. A recent comparison of these studies [17] indicated that even though the results identified common pathways that are being modulated upon infection, there was less consistency in identifying individual proteins.…”
Section: Introductionmentioning
confidence: 99%